THE ROLE OF THEORETICAL GRAMMAR IN UNDERSTANDING LANGUAGE STRUCTURE AND MEANING (International Congress on Economics, Management and Business Studies, 2026)
This article provides an in-depth analysis of theoretical grammar as a fundamental branch of linguistics. It explores the principles, components, and functions of theoretical grammar in understanding language structure and meaning. The paper distinguishes theoretical grammar from practical grammar and examines its core areas such as morphology, syntax, semantics, and pragmatics. Additionally, the article highlights the role of theoretical grammar in modern language teaching and linguistic research. The study emphasizes that theoretical grammar is essential for developing analytical thinking and improving language competence.
Keywords: Theoretical grammar, morphology, syntax, semantics, pragmatics, linguistic theory, language structure, generative grammar, transformational grammar, communication.